THE EFFECTS OF TAMOXIFEN AND CHEMOTHERAPY AFTER SURGERY ON THE RECURRENCE AND SURVIVAL OF BREAST CANCER PATIENTS WITH POSITIVE HORMONE RECEPTOR: A META-ANALYSIS - Delimasari, Trisakti Halimah; Tamtomo, Didik; Murti, Bhisma (Indonesian Journal of Medicine, 2019)
Background: Breast cancer is the most common type of cancer suffered by women in the world. The combination of tamoxifen and chemotherapy significantly reduces the risk of recurrence and mortality in breast cancer patients. This study aimed to analyze how effective the combination of tamoxifen and chemotherapy after surgery to reduce the risk of recurrence and mortality in breast cancer patients with positive hormone receptor.Subjects and Method: This study used systematic review and meta-analysis. The researcher collected articles from the Pubmed journal database. The subjects of the study were women with breast cancer after surgery. The dependent variable was recurrence and survival (mortality). The independent variables were tamoxifen and chemotherapy. Data were analyzed based on the fixed and random effects model using RevMan 5 software.Results: There were 3 articles with 3,761 women who were involved in the analysis process. The combination of tamoxifen and chemotherapy could reduce the risk of recurrence in women with positive hormone receptor (ER+) breast cancer (HR=0.68; 95%CI=0.58 to 0.80; p=0.001). The combination of tamoxifen and chemotherapy showed weak and non-significant decreasing trend in reducing the risk of mortality in women with ER+breast cancer (HR=0.87; 95%CI=0.73 to 1.03; p= 0.11).Conclusion: The combination of tamoxifen and chemotherapy in women with ER+ breast cancer is effective in reducing the risk of recurrence. However, it does not increase survival.Keywords: tamoxifen, chemotherapy, breast cancer.Correspondence:Trisakti Halimah Delimasari. Program Studi Ilmu Kesehatan Kesehatan, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: trisaktihd1994@gmail.com. Mobile: +6285 293 994 629.Indonesian Journal of Medicine (2019), 4(4): 346-353https://doi.org/10.26911/theijmed.2019.04.04.07